Critical Thinking Development of Primary School Pupils by Means of Inventive Problems - Gavrysh, Iryna; Dotsenko, Svitlana (Educational Challenges, 2021)
The purpose of the research is to determine the effective tools for the critical thinking development for primary school pupils. Methodology. The retrospective analysis of the primary education systems development in Ukraine and in highly developed countries was used, the primary school is determined to be the initial stage of the pupils’ critical thinking development. The material of the study is primary school educational programmes, branches of education, and existing academic subjects, it indicates the necessity to develop and implement the particular subject, and its aim is to develop critical thinking and the abilities to express one’s own opinion, assess risks and solve problems. According to the State Standard of Primary Education the key competencies require the following skills: creativity; initiative; the abilities to justify one’s position logically, to manage emotions constructively, to assess risks, to make decisions, to solve problems, to cooperate with others. Results. The article clarifies that critical thinking is a type of thinking aimed at solving problems, namely studying the argument line (hypotheses, criteria, definitions, arguments, facts, etc.), analyzing alternative solutions; forecasting and assessing consequences. It is proved in practice that inventive problems serve as an effective way to develop critical thinking. The basis of such problems is the theory of inventive problem solving (TIPS). It is determined that an inventive problem contains a cognitive contradiction, its solving promotes the pupils’ critical thinking development. The authors’ subject ‘Eureka’ for pupils of 2-4 classes is offered. Its aim is to develop pupils’ critical thinking, creative and inventive abilities, and also primary skills to carry out natural science researches. The results of the subject approbation are given. Conclusions. Primary school pupils’ critical thinking development can be achieved through the introduction of a range of new subjects at the initial stages of education. The aim of such subjects is to teach pupils to solve inventive problems.